The effects of tislelizumab plus chemotherapy as first-line treatment on health-related quality of life of patients with advanced squamous non-small cell lung cancer: Results from a phase 3 randomized clinical trial. (2022) - Wang, J; Yu, X; Barnes, G; Leaw, S; Bao, Y; Tang, B
Clinical practice points: During the chemotherapy era, the standard first-line therapy for patients with advanced squamous NSCLC (sq-NSCLC) without targetable genetic aberrations was platinum-doublet chemotherapy. However, the efficacy of platinum-doublet chemotherapy is limited with response rates of only 20%, and a median overall survival of less than 1 year. The RATIONALE 307 trial demonstrated that tislelizumab, a PD-1 inhibitor, added to platinum-based chemotherapy significantly improved progression-free survival versus chemotherapy alone in patients with advanced squamous non-small cell lung cancer (sq-NSCLC). It is well reported that patients with NSCLC usually suffer from several disease-related symptoms which negatively affect their health-related quality of life (HRQoL). This study represents the first report that HRQoL was specifically assessed in sq-NSCLC patients receiving PD-1 inhibitor therapy as all other HRQoL data to date include sq- and nonsquamous NSCLC The addition of tislelizumab to platinum-based chemotherapy was associated with improvements in sq-NSCLC patients' overall HRQoL as well as lung cancer–specific symptoms including coughing, dyspnea, and hemoptysis. These results, along with the efficacy and safety results, demonstrate a favorable risk-benefit ratio of tislelizumab in combination with carboplatin and paclitaxel or nab-paclitaxel as first-line treatment of patients with advanced sq-NSCLC. Abstract: Background: This study assessed the effects of adding tislelizumab to first-line standard-of- care chemotherapy on the health-related quality of life (HRQoL) of patients with advanced squamous non-small cell lung cancer (sq-NSCLC). Patients and methods: Patients in this open-label, multicenter, phase 3 RATIONALE 307 trial were randomized to one of the three arms: tislelizumab plus carboplatin and paclitaxel (Arm A), tislelizumab plus carboplatin and nab-paclitaxel (Arm B), or paclitaxel plus carboplatin (Arm C). HRQoL was measured using the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) and the EORTC Quality of Life Questionnaire Lung Cancer 13-item module (QLQ-LC13). Mean score change from baseline at Weeks 6 and 12 in the QLQ-C30's global health status/quality of life (GHS/QoL), fatigue, and physical functioning scores and QLQ-LC13 lung cancer specific subscales were examined. Time to deterioration was estimated for the GHS/QoL score. Results: A total of 355 sq-NSCLC patients received at least one dose of study drug and completed at least one HRQoL assessment. The GHS/QoL scores improved in Arms A and B relative to Arm C at Weeks 6 and 12. Arms A and B also experienced a reduction in most lung cancer-specific symptoms relative to Arm C. Time to deterioration of GHS/QoL was not reached by any of the three arms. Conclusions: The addition of tislelizumab to platinum-based chemotherapy is associated with improvements in sq-NSCLC patients' HRQoL, especially in GHS/QoL and most importantly in lung cancer-specific symptoms including coughing, dyspnea, and hemoptysis.